Integration of Expectation-Confirmation Model and Task-Technology Fit: Its Impact on Cloud-Based E-Learning Sustainability in Educational Institutions - Nurhasanah, Sri Utami; Fitriyani, Sarah (Journal of Economic and Leadership, 2024)
This study aims to explore the integration of the Expectation-Confirmation Model (ECM) and Task-Technology Fit (TTF) in understanding the sustainability of cloud-based e-learning in educational institutions. Using a qualitative literature review approach, this research examines relevant prior studies to analyze the relationship between task-technology fit, expectation confirmation, and users' continuance intention. The findings reveal that the alignment between e-learning technology features and users' task needs significantly contributes to perceived usefulness and satisfaction, ultimately driving continuance intention. Additionally, external factors such as institutional support and system quality play crucial roles in sustaining usage. The integration of ECM and TTF provides a more comprehensive analytical framework to explain users' post-adoption behavior towards cloud-based e-learning. However, this study has several limitations, including the lack of empirical data and a limited focus on social dynamics and psychological factors. This research offers significant contributions to the development of sustainable e-learning implementation strategies and recommends further studies to address the identified limitations.